the "Development of LKPD Based on PBL Model Assisted by Interactive Multimedia to Improve Science Process Skills of Grade V Elementary School Students - Aprilia, Isnainiatun; Widi Winarni, Endang; Muktadir, Abdul (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2025)
The purpose of this research is to develop a LKPD product based on the PBL model with the help of interactive multimedia to improve the science process skills of fifth-grade elementary school students. The type of research used is R&D. The types of data used are quantitative and qualitative data; quantitative data using score questionnaires provided by validators, while qualitative data consist of feedback and suggestions from expert validation. Based on the research results, it was found that the difference in pretest and posttest scores showed an improvement in the science process skills of fifth-grade students at SD Negeri 126 Rejang Lebong, with an average pretest score of 55 and an average posttest score of 85.25, and the N-Gain Score test results also showed an average of 83.85, categorized as high. Based on the research results, it can be concluded that LKPD can improve the science process skills of fifth-grade elementary school students.